Grey-Level Cooccurrence Matrix Performance Evaluation For Heading Angle Estimation Of Moveable Vision System In Static Environment - Zainal, Zairulazha; Ramli, Rizauddin; Mustafa, Mohd Marzuki (Hindawi Publishing Corporation, 2013)
A method of extracting information in estimating heading angle of vision system is presented. Integration of grey-level cooccurrence matrix (GLCM) in an area of interest selection is carried out to choose a suitable region that is feasible for optical flow generation. The selected area is employed for optical flow generation by using Horn-Schunck method. From the generated optical flow, heading angle is estimated and enhanced via moving median filter (MMF). In order to ascertain the effectiveness of GLCM, we compared the result with a different estimation method of optical flow which is generated directly from untouched greyscale images. The performance of GLCM is compared to the true heading, and the error is evaluated through mean absolute deviation (MAE). The result ensured that GLCM can improve the estimation result of the heading angle of vision system significantly.